Globally Engaged and Locally Relevant: Revisiting Higher Education - Ilieva, Janet; Tsiligiris, Vangelis (International Higher Education, 2021)
This article examines current pressures on higher education provision and attempts to draw long-term considerations for institutions and policy makers. It calls for a reconceptualization of international higher education, placing global citizenship at the core of its provision. Such education delivery aims to be locally embedded, globally relevant, and centered on the needs and ambitions of a diverse student population.